Antibacterial Activity of Dendrophthoe pentandra (L.) Leaves Extract Against Staphylococcus aureus and Escherichia coli - Inggrid, Annabelle Marie; Aditiyarini, Dwi; Prakasita, Vinsa Cantya (Jurnal Biodjati, 2024)
Sapuran, Wonosobo is a popular area with several local tea plantations, which are infested by mistletoe, such as Dendrophthoe pentandra (L.) Miq. Mistletoe has been widely reported to have antibacterial activity due to its secondary metabolite content. Therefore, this study aimed to identify and explore the antibacterial activity of D. pentandra leaves extract against Staphylococcus aureus and Escherichia coli. The test samples were extracted using the maceration method, followed by phytochemical screening and total assay of flavonoids, phenols, and tannins. Antibacterial activity tests were carried out using disk diffusion, Minimum Inhibitory Concentration (MIC), and Minimum Bactericidal Concentration (MBC). The yield from the maceration method using 96% ethanol solvent was 8.78%, containing secondary metabolite compounds, including alkaloids, saponins, steroids, terpenoids, and flavonoids. The total flavonoid, phenol, and tanin content obtained were 4.09 ± 0.70 mg QE/g, 1.76 ± 0.16 g GAE/g, and 1.37 ± 0.14 mg TAE/g, respectively. In addition, the extract showed medium inhibition of S. aureus at a concentration of 400 and 525 mg/m, with no inhibitory effect against E. coli. The MIC and MBC from the microdilution method for S. aureus were at 4400 and 8800 mg/mL extract, while values of 28000 and 56000 mg/mL were obtained for E. coli. Based on these results, the inhibition activity of ethanol extract of D. pentandra against S. aureus was greater compared to E. coli.